VARIASI UKURAN DUA BUAH LUKISAN DALAM SEBUAH RUANG PAMERAN BERPENGARUH TERHADAP KENYAMANAN PENGUNJUNG PAMERAN - Widnyana, I Gusti Nyoman (Universitas Pendidikan Ganesha, 2014)
The ergonomic problems found in the painting exhibition gallery indicated that: some paintings were displayed without considering the room size, so it would give effect that the paintings themselves seemed to be so small or on the other way around that they would be likely too big, this would affect the visitorsâ€™ comfort when they try to watch the exhibition. In order to solve the problems, a study on the ergonomic aspect needed to be conducted based on the comparison between the painting and the room size, so that the exhibition visitors would feel comfortable when viewing the paintings themselves. The study was conducted in the â€œXâ€ gallery in Ubud, Gianyar. The subjects involved 20 different individuals. It utilized a treatment by subject design which was developed into two-period cross over design with the total members of the first group ( PO ) of 10 persons and the second group ( PO ) of about 10 persons. The independent variable of the study was the size variety of the painting including 50 cm X 60 cm and 150 cm x 200 cm. The dependent variable included the comfort while viewing the exhibition. On the first period in a room with 6 m x 4 m x 3 m wide, while the first group viewed the painting with 150 cm x 200 cm wide and the second group viewing a painting with 50 cm x 60 cm wide. Then a washing out was conducted for as long as two days. After that in a second period the second group viewed the painting with 50 cm x 60 cm wide, while the first viewed the painting with 150 cm x 200 cm wide. The comfort ability viewing the painting was measured by using a set of questionnaire with 5 Likert scales. The results would be tested by using Wilcoxon test. The results indicated that there was a significant difference (with p<0.05) between the score of general fatigue of the first group, such as 60.72 and the second group of 54.83. or a declining of 9.7%. While in terms of the comfort scores, there was a significant difference between the first group of 54.89 and the second group of 73.88 or improved up to 34.6%. It could be concluded that (1) there was a significant difference between the exhibition visitorsâ€™ comfort when viewing the painting of 50 cm x 60 cm and 150 cm x 200 cm wide in the exhibition room of 6 m x 4 m x 3 m wide, (2) the exhibition visitorsâ€™ comfort when viewing the painting of 50 cm x 60 cm wide was better than that when viewing the painting of 150 cm x 200 cm wide inside the exhibition room of 4 m x 6 m x 3 m.Key-words: painting size, exhibition room (hall), viewing comfort